2020
DOI: 10.1007/s11196-020-09738-1
|View full text |Cite
|
Sign up to set email alerts
|

So Close and Yet So Far: The Distant Heritage of the Historical Urban Landscapes of Residential Districts of Tartu, Estonia

Abstract: The urban landscapes of residential areas outside of historic city centres have been increasingly recognized as cultural heritage and as potentially powerful source of meaning for local identities. In Estonia, many municipalities have established milieu protection areas, among them the town of Tartu which has currently ten areas, mainly comprising residential areas developed in the late nineteenth and early twentieth century. The authorised heritage discourse proceeds from the historical values in these areas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…It can kill creativity and divert focus from the original goal. Also Kallast (2021) has showed that the Estonian authorised heritage discourse has focused on setting restrictive measures for construction and renovation works instead of properly communicating the historical values.…”
Section: Questionnaire and Evaluationmentioning
confidence: 99%
“…It can kill creativity and divert focus from the original goal. Also Kallast (2021) has showed that the Estonian authorised heritage discourse has focused on setting restrictive measures for construction and renovation works instead of properly communicating the historical values.…”
Section: Questionnaire and Evaluationmentioning
confidence: 99%